"A Strong-Minded American Lady": Bloomerism in Texts and Images, 1851. (7th August 2016) - Petrov, Julia
Abstract: This paper offers new perspectives on the reception of the women's dress reform movement in Britain and North America. Focusing on a central case study of a satirical letter and accompanying illustration parodying Bloomerism, which was published on both sides of the Atlantic, periodical editorials are analyzed in light of contemporary social and political attitudes. In contrast to commonly held assumptions about Bloomerism having failed because of deeply entrenched gender norms, it is instead asserted that the eventual backlash against the Bloomer fashion was a result of the British association with America's poor showing at the Great Exhibition in London in 1851, and not necessarily because of inherent objections to its sartorial aesthetics.